Implementing best practice for peripheral intravenous cannula use in Australian emergency departments: a stepped-wedge cluster-controlled trial and health economic analysis protocol - Gerben Keijzers; Cathrine Mihalopoulos; Peter Cameron; Emily Callander; Louise Cullen; Gerard O’Reilly; Diana Egerton-Warburton; Helena J Teede; Joanne Enticott; Carolyn Hullick; Daniel Fatovich; Claire Rickard; et al. (BMJ Open)
Introduction Over one billion adults attend emergency departments (EDs) internationally every year, including 6.6 million in Australia. Up to half of these patients have a peripheral intravenous catheter (PIVC) inserted. Although healthcare workers believe that placing a cannula is helpful (‘just in case’), PIVCs often remain idle. PIVC insertion is painful for patients, takes clinicians’ attention away from other care, has adverse outcomes and causes major economic and environmental burden. Our aim is to codesign an implementation toolkit to reduce unnecessary PIVC insertions and improve other national quality indicators using an implementation science framework.Methods and analysis A stepped-wedge cluster-controlled trial will be conducted in nine ED sites (clusters) across Australia. The interventions will be codesigned with and adapted to sites based on local context. The interventions are evidence-based multimodal intervention (MMI) and aligned to the 2021 Australian Commission for Safety and Quality in Health Care National PIVC Clinical Care Standard. The Consolidated Framework for Implementation Research and Learning Health System will be used to guide implementation. Interventions will be phased across three steps (three sites per step), and each site will collect control and postintervention data using mainly routinely collected clinical data. Each site will be allocated to receive the intervention at one of three study steps. Implementation strategies will tailor broad clinician and consumer engagement, policy changes, education, audit and feedback and clinical champions, along with environment and equipment changes, to each site. The primary objective is to reduce the proportion of adult patients who have a PIVC inserted by 10%. We will evaluate the clinical, implementation and cost-effectiveness of the intervention.Study findings will be used to conduct a health economic analysis, develop an implementation toolkit and inform a sustainable roadmap for national roll-out. This will meet the needs of a diverse range of EDs nationally and internationally.Ethics and dissemination The protocol was approved by the Monash Health Human Research Ethics Committee (HREC Reference Number: HREC/100808/MonH-2023-390692(v3)). The outcomes of this trial will be disseminated through peer-reviewed publications, conference presentations and communication with study partners and stakeholders including professional colleges and the Australian Commission for Safety and Quality in Health Care.Trial registration number Australian New Zealand Clinical Trials Registry registration number: ACTRN12623001248651. Date of registration: 1 December 2023. https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=386256&showOriginal=true&isReview=true